Paths of Fire : An Anthropologist's Inquiry into Western Technology - Adams, Robert M. (Book collections on Project MUSE., 2001)
Technology, perhaps the most salient feature of our time, affects everything from jobs to international law yet ranks among the most unpredictable facets of human life. Here Robert McC. Adams, renowned anthropologist and Secretary Emeritus of the Smithsonian Institution, builds a new approach to understanding the circumstances that drive technological change, stressing its episodic, irregular nature. The result is nothing less than a sweeping history of technological transformation from ancient times until now. Rare in antiquity, the bursts of innovations that mark the advance of technology ha.